(untitled) (Fiep Bulletin - online, 2011)
Currently in Brazil, increasingly, there is a framework for older people who acquire illnesses and become dependent, and need, often in one or more persons to meet their functional impairments at home, so that they can perform their activities of daily living. In this sense, willing to discuss and disseminate the available literature on the caregivers of dependent elderly at home, this study aims to identify how the role of caregiver has been described in literature. This is a descriptive study literature review, carried out a literature on the theme of caregivers of dependent elderly in electronic databases LILACS and BDENF. After applying the criteria for inclusion and exclusion, has become a sample of 41 studies, among them, the more thematic approach that has been brought on to the "Caregivers of elderly with dementia, followed by "Caregiver’s profile for the elderly ", and others such as" Stress on the caregiver, caretaker of elderly patients with cancer, "Caregiver age in LPI," among others. After the analysis of these studies, we noticed that it is essential that corporate actions on the part of health team to monitor elderly family, carevigers and their families, to direct the care relationship, and promoting interaction with the community, avoid physical harm and social isolation which often the caregiver and the elderly undergo.